Risk of Positive Nonsentinel Nodes in Women with 1–2 Positive Sentinel Nodes Related to Age and Molecular Subtype Approximated by Receptor Status. Issue 4 (26th May 2014) - Freedman, Gary M.; Fowble, Barbara L.; Li, Tianyu; Hwang, E. Shelley; Schechter, Naomi; Devarajan, Karthik; Anderson, Penny R.; Sigurdson, Elin R.; Goldstein, Lori J.; Bleicher, Richard J.
Abstract We examine risk of positive nonsentinel axillary nodes (NSN) and ≥4 positive nodes in patients with 1–2 positive sentinel nodes (SN) by age and tumor subtype approximated by ER, PR, and Her2 receptor status. Review of two institutional databases demonstrated 284 women undergoing breast conservation between 1997 and 2008 for T1‐2 tumors and 1 (229) or 2 (55) positive SN followed by completion dissection. The median number of SN and total axillary nodes removed were 2 (range 1–10) and 14 (range 6–37), respectively. The rate of positive NSNs (p = 0.5) or ≥4 positive nodes (p = 0.6) was not associated with age. NSN were positive in 36% of luminal A, 26% of luminal B, 21% of TN and 38% of Her2+ (p = 0.4). Four or more nodes were present in 17% of luminal A, 13% luminal of B, 0% of TN and 29% of Her2+ (p = 0.1). Microscopic extracapsular extension was significantly associated with having NSNs positive (55% versus 24%, p < 0.0001) and with having total ≥4 nodes positive (33% versus 7%, p < 0.0001). In a population that was largely eligible for ACOSOG Z0011, the risk of positive NSN or ≥4 positive nodes did not vary significantly by age. The TN subgroup had the lowest risk of both positive NSN or ≥4 positive nodes. Several high risk groups with >15% risk for having ≥4 positive nodes were identified. Further data is needed to confirm that ACOSOG Z0011 results are equally applicable to all molecular phenotypes.